Seleção e caracterização de peptídeos recombinantes ligantes a anticorpos monoclonais reativos a proteínas de Anaplasma marginale - Cunha, Vanessa Rodrigues Borges da (2008)
Bovine anaplasmosis is caused by Anaplasma marginale and A. centrale. The most pathogenic and important species for cattle production is A. marginale, and is widely distributed in tropical, subtropical and temperate regions of the world. A. marginale is an intra-erythrocyte rickettsia of susceptible ruminants, biological and mechanically transmitted by ticks and hematophagous insects. The tick Rhipicephalus (Boophilus) microplus is the main vector of A. marginale in Brazil. The congenital form of transmission in cattle may occur, causing the neonatal anaplasmosis. The outer membrane of A. marginale includes six well characterized major surface proteins, MSP1a, MSP1b, MSP2, MSP3, MSP4 and MSP5, which play important role in the development of the immune response of infected animals. In this study, we have used the Phage Display technology to identify specific peptides that were immunoreactive to monoclonal antibodies anti-A. marginale proteins. Peptide selection was performed using a subtractive selection of a peptide library with 12 random amino acids, Ph.D.-12, expressed on the surface of the M13 filamentous phage concurrently against the anti-MSP1a and anti-MSP2. After four rounds of selection and validation by ELISA, the selected peptides have recognized only the anti-MSP1. Analysis of bioinformatics identified 45 peptides, which showed the protein consensus sequence STxS that was represented in 78% of selected phages. Due to the multiple motif repeats found in MSP1 protein, the STSSxL motif may become an important biological target, with potential use in diagnostic tests and vaccine for the control of Anaplasma marginale.